Вплив факторів зовнішнього середовища підприємства на концепцію управління конкурентним потенціалом підприємства - Кравченко, М. С.; Романчук, Р. С.; Будагян, А. С.; Kravchenko, M.; Romanchuk, R.; Budahian, А. (ЦНТУ, 2025)
Стаття присвячена проблемі впливу факторів зовнішнього середовища на управління конкурентним потенціалом підприємства. Фактори зовнішнього середовища мають значний вплив на управління конкурентним потенціалом підприємства через те, що зміни в економічних умовах, політичній ситуації, технологіях, соціальних тенденціях та конкурентному середовищі змушують підприємства адаптувати свої стратегії та концепції управління для підтримки конкурентоспроможності. The article is devoted to the problem of the influence of external environmental factors on the management of the competitive potential of an enterprise. External environmental factors have a significant impact on the management of the competitive potential of an enterprise due to the fact that changes in economic conditions, political situation, technologies, social trends and the competitive environment force enterprises to adapt their strategies and management concepts to maintain competitiveness.
The Influence of the Factors of the Enterprise's External Environment on the Concept of Management of the Enterprise's Competitive Potential
Keywords: підприємство; зовнішнє середовище; потенціал; конкуренція; enterprise; external environment; competitive potential; competition